2016
DOI: 10.1103/physrevlett.117.256103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Passive Lossless Metasurfaces Using Auxiliary Fields for Reflectionless Beam Splitting and Perfect Reflection

Abstract: We introduce a paradigm for accurate design of metasurfaces for intricate beam manipulation, implementing functionalities previously considered impossible to achieve with passive lossless elements. The key concept involves self-generation of auxiliary evanescent fields which facilitate the required local power conservation, without interfering with the device performance in the far field.We demonstrate our scheme by presenting exact reactive solutions to the challenging problems of reflectionless beam splittin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
235
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 308 publications
(242 citation statements)
references
References 31 publications
7
235
0
Order By: Relevance
“…To ensure maximum signal reflection, existing works on RIS-assisted systems set α = 1, justifying this choice with the significant research progress made on the development of lossless metasurfaces that can achieve unity reflection magnitude with arbitrary reflection phase [25]- [28].…”
Section: A Signal Modelmentioning
confidence: 99%
“…To ensure maximum signal reflection, existing works on RIS-assisted systems set α = 1, justifying this choice with the significant research progress made on the development of lossless metasurfaces that can achieve unity reflection magnitude with arbitrary reflection phase [25]- [28].…”
Section: A Signal Modelmentioning
confidence: 99%
“…For this purpose, we use a synthesis method based on generalized Snell's laws which intuitively allows for arbitrary control of reflected and transmitted waves through local phase shifts at the metasurface. It should be mentioned that this synthesize method suffers in terms of power efficiency due to spurious scattering and it has been recently found that the ideal required phase shift differs from the prescription of the generalized Snell's law [77][78][79]. However, due to the 2π phase span provided by the proposed design paradigm, it can be used flexibly in more sophisticated synthesis methods to improve the efficiency of functionality.…”
Section: Wavefront Engineering Of Generated Frequency Harmonicsmentioning
confidence: 99%
“…Based on this approach, however, transforming an incident wave towards an arbitrary direction with unitary efficiency in general requires locally active or strongly non-local metasurfaces [18]- [19]. Using the interference with auxiliary evanescent modes [23] or leaky modes [24], one can engineer passive impedance profiles that emulate the required non-local effects and get close to unitary efficiency. Such metasurfaces, however, are still subject to implementation difficulties when the limited fabrication resolution are considered, since they also require the discretization of a continuous, fastly varying, impedance profile.…”
mentioning
confidence: 99%